Coping With Difficulties In Teaching Speaking For Students Of Department Of English Education Of Universitas Muhammadiyah Surakarta In 2016 Academic Year - Fitria, Indah Musfirotul, Fitri Kurniawan, M. Res, Ed (2017)
The objective of the research is to describe the difficulties in teaching speaking and the strategies used in teaching speaking learning process faced by the lecturer of Speaking on Discussion and Debate in Department of English Education of Universitas Muhammadiyah Surakarta in 2016 academic year. The type of the research is descriptive qualitative research. The researcher applies a case study, such as, observation and interview. The subject of the research is the speaking lecturer of Universitas Muhammadiyah Surakarta who teaches the third semester. The method of collecting data are observation and interview. To analyze qualitative data the researcher applied reduction the data, presentation and Verification of the Data. The result of this research shows that there are some difficulties in teaching speaking faced by the lecturer, namely: student's ability, the discipline's students are less. However, there is one main difficulty that influences the next steps taken by the interviewee regarding the lecturer's strategies to cope with her difficulties. The biggest problem is that the lecturer felt confused to apply the materials which is suitable for the students, because there are two choices material. In addition, to cope with those difficulties, the lecturer uses five strategies such as a personal decision, alternative method, alternative material, alternative approach, and students and a head of department's aspiration. Hence, the lecturer cope with the existing difficulties and the students seemed more interested in speaking 3 material.